The Effect of Anemia Education Through Animated Video Media on the Behavior and Compliance of Taking Iron Supplement Tablets among Students of SMPN 31 Medan - Ayu Wulandari Andri Dalimunthe (Jurnal Kesehatan Masyarakat Perkotaan, 2026)
Anemia is a public health problem that is still often found in adolescent age groups, especially adolescent girls. Anemia in adolescent girls remains a health problem that impacts fitness, concentration, and academic achievement, so an effective educational strategy is needed to increase the consumption of Iron Supplement Tablets (TTD). This study aims to analyze the effect of anemia education through animated video media on knowledge, attitudes, and compliance with TTD consumption in female students of SMPN 31 Medan. The study used a quasi-experimental design with a one-group pre-test post-test design and involved 56 eighth-grade female students. The intervention was in the form of playing an educational animated video with a duration of ± 3 minutes, while the instruments included a knowledge questionnaire, an attitude questionnaire, and a compliance control card. Analysis used the Wilcoxon test. The results showed a significant increase in knowledge, attitudes, and compliance after education, with a p value of 0.000 each (p < 0.05). Knowledge in the good category increased from 33.9% to 100%, good attitude increased from 28.6% to 66.1%, and compliance from completely non-compliant changed to 57.1% compliant. The conclusion of the study shows that anemia education through animated videos is effective in increasing understanding, forming positive attitudes, and encouraging compliance with iron supplement consumption in adolescent girls, so it is worthy of being recommended as a promotional education medium in schools.